Mutations in the histone fold domain of the TAF12 gene show synthetic lethality with the TAF1 gene lacking the TAF N-terminal domain (TAND) by different mechanisms from those in the SPT15 gene encoding the TATA box-binding protein (TBP) - Kobayashi, Akiko (Oxford University Press, 2003)
The general transcription factor TFIID, composed of the TATA box-binding protein (TBP) and 14 TBP-associated factors (TAFs), is important for both basal and regulated transcription by RNA polymerase II. Although it is well known that the TAF N-terminal domain (TAND) at the amino-terminus of the TAF1 protein binds to TBP and thereby inhibits TBP function in vitro, the physiological role of this domain remains obscure. In our previous study, we screened for mutations that cause lethality when co-expressed with the TAF1 gene lacking TAND (taf1-ΔTAND) and identified two ΔTAND synthetic lethal (nsl) mutations as those in the SPT15 gene encoding TBP. In this study we isolated another nsl mutation in the same screen and identified it to be a mutation in the histone fold domain (HFD) of the TAF12 gene. Several other HFD mutations of this gene also exhibit nsl phenotypes, and all of them are more or less impaired in transcriptional activation in vivo. Interestingly, a set of genes affected in the taf1-ΔTAND mutant is similarly affected in the taf12 HFD mutants but not in the nsl mutants of TBP. Therefore, we discovered that the nsl mutations of these two genes cause lethality in the taf1-ΔTAND mutant by different mechanisms.